Complications in Brachioplasty: A Systematic Review and Meta-Analysis. Issue 1 (21st December 2021) - Aljerian, Albaraa; Abi-Rafeh, Jad; Ramirez-GarciaLuna, José; Hemmerling, Thomas; Gilardino, Mirko S.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Brachioplasty procedures have experienced a surge in popularity over the past decade, mirroring the rise in bariatric procedures and growing population of massive weight loss patients. The authors estimated the incidence of associated complications and identify possible patient- or procedure-related predictive factors. Methods: A systematic review was performed using the PubMed, Cochrane, and Embase databases; extracted data were synthesized through a random-effects meta-analysis of proportions and a multivariate meta-regression. Results: Twenty-nine studies were included in the meta-analysis, representing 1578 patients; all studies followed an observational design. The incidence of adverse outcomes assessed included aberrant scarring, 9.9 percent (95 percent CI, 6.1 to 15.6 percent); ptosis or recurrence, 7.79 percent (95 percent CI, 4.8 to 12.35 percent); wound dehiscence, 6.81 percent (95 percent CI, 4.63 to 9.90 percent); seroma, 5.91 percent (95 percent CI, 3.75 to 9.25 percent); infection, 3.64 percent (95 percent CI, 2.38 to 5.53 percent); nerve-related complications, 2.47 percent (95 percent CI, 1.45 to 4.18 percent); lymphedema or lymphocele formation, 2.46 percent (95 percent CI, 1.55 to 3.88 percent); skin necrosis or delayed healing, 2.27 percent (95 percent CI, 1.37 to 3.74 percent); and hematoma, 2.06 percent (95 percent CI, 1.38 to 3.06 percent). The operative reintervention rate for aesthetic purposes was 7.46 percent (95 percent CI, 5.05 to 10.88 percent), and the operative reintervention rate for nonaesthetic purposes was 1.62 percent (95 percent CI, 1.00 to 2.61 percent). Multivariate meta-regression demonstrated that medial incision placement was associated with a higher risk of complications, whereas the incidence of certain complications was lowered with adjunctive liposuction ( p < 0.05). Conclusion: In the absence of large clinical trials, the present meta-analysis can serve to provide plastic surgeons with an evidence-based reference to improve informed consent and guide procedure selection with respect to the complication profile of brachioplasty.